DEVELOPING CREATIVE COMPETENCE IN STUDENTS THROUGH INDEPENDENT LEARNING ACTIVITIES: A CASE STUDY OF PROBLEM-BASED AND PROJECT-BASED LEARNING (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This study investigates the role of problem-based and project-based learning methods in enhancing students’ creative competence during independent learning activities. Conducted with higher education students in Uzbekistan, the research employs an experimental design involving two groups: an experimental group utilizing innovative pedagogical methods and a control group relying on traditional teaching approaches. Data collection was achieved through Torrance creativity tests, surveys with 80 students and 30 teachers, and practical observations.Key findings reveal that problem-based and project-based learning approaches contributed to a 19% improvement in creativity across four dimensions: fluency, flexibility, originality, and elaboration, compared to minimal improvements in the control group. Surveys indicate that 75% of students and 80% of teachers consider these methods more effective in promoting creativity. These results demonstrate the necessity of incorporating innovative approaches into independent learning frameworks to develop creative competence.